1996
DOI: 10.1103/physrevb.53.7010
|View full text |Cite
|
Sign up to set email alerts
|

Berry phase, hyperorbits, and the Hofstadter spectrum: Semiclassical dynamics in magnetic Bloch bands

Abstract: We have derived a new set of semiclassical equations for electrons in magnetic Bloch bands. The velocity and energy of magnetic Bloch electrons are found to be modified by the Berry phase and magnetization. This semiclassical approach is used to study general electron transport in a DC or AC electric field. We also find a close connection between the cyclotron orbits in magnetic Bloch bands and the energy subbands in the Hofstadter spectrum. Based on this formalism, the pattern of band splitting, the distribut… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
495
2
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 563 publications
(501 citation statements)
references
References 48 publications
3
495
2
1
Order By: Relevance
“…One of the most interesting properties of gapped bilayer graphene is the existence of a finite Hall conductivity and orbital magnetism due to the flavor-dependent momentumspace vortices 14,17,30 in the broken symmetry states. Because the vorticity v is opposite for opposite valleys, the integrated Berry curvature gives rise to a Hall conductivity 18,19,31,32 with magnitude e 2 /h for each flavor, and a sign that changes with valley as well as with layer polarization. The Berry curvature reflects the handedness of Bloch electrons and captures intracell circulating currents which generate a finite orbital magnetic moment proportional to the angular momentum due to self-rotating Bloch wave packets.…”
Section: A Total Layer Density and Chern Number Classifications Of Cmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the most interesting properties of gapped bilayer graphene is the existence of a finite Hall conductivity and orbital magnetism due to the flavor-dependent momentumspace vortices 14,17,30 in the broken symmetry states. Because the vorticity v is opposite for opposite valleys, the integrated Berry curvature gives rise to a Hall conductivity 18,19,31,32 with magnitude e 2 /h for each flavor, and a sign that changes with valley as well as with layer polarization. The Berry curvature reflects the handedness of Bloch electrons and captures intracell circulating currents which generate a finite orbital magnetic moment proportional to the angular momentum due to self-rotating Bloch wave packets.…”
Section: A Total Layer Density and Chern Number Classifications Of Cmentioning
confidence: 99%
“…The Berry curvature reflects the handedness of Bloch electrons and captures intracell circulating currents which generate a finite orbital magnetic moment proportional to the angular momentum due to self-rotating Bloch wave packets. 32 The Berry curvature of the system can be evaluated using 18…”
Section: A Total Layer Density and Chern Number Classifications Of Cmentioning
confidence: 99%
“…Interestingly, this intrinsic mechanism has recently been reinterpreted in terms of the Berry curvature of the occupied Bloch states. [7][8][9] Furthermore, recent first-principles studies based on the Berry phase formalism showed that the intrinsic AHE is important in various materials. 10,11 In particular, in itinerant ferromagnets such as Fe, the intrinsic AHC given by firstprinciples density functional calculations with the generalized gradient approximation (GGA) 10 has been found to agree rather well with the experimental AHC 12,13 .…”
Section: Introductionmentioning
confidence: 99%
“…As an electron wavepacket moves in kspace under the influence of an applied field, there are two contributions to its spatial velocity v. The first term, the group velocity, describes how the modified energy-momentum relation changes the velocity of the center of a wavepacket, which is an effect that would be present even for a point particle. The Karplus-Luttinger contribution, which can be derived quite systematically 6,23 , describes how a change in k induces a change in the real-space location because the Bloch states are changing: this change is…”
Section: Key Features Of the Anomalous Hall Effectmentioning
confidence: 99%